2014
DOI: 10.1007/978-1-4939-1372-5_4
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Nitric Oxide, Neurotrophins and HPA Axis in Neurobehavioural Alterations Induced by Prenatal Stress

Abstract: Several studies suggest that negative emotions during pregnancy generate adverse effects on the cognitive, behavioural and emotional development of the descendants. The psychoneuroendocrine pathways involve the transplacentary passage of maternal glucocorticoids in order to influence directly on fetal growth and brain development.Nitric oxide is a gaseous neurotransmitter that plays an important role in the control of neural activity by diffusing into neurons and participates in learning and memory processes. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 95 publications
0
3
0
Order By: Relevance
“…When stress affects the expression of GR in the hippocampus, the negative feedback regulation of the HPA axis will be affected. Many experimental studies have also confirmed that the presence of long-term increased GC will reduce the expression of GR, weaken the inhibition of the HPA axis and make the HPA axis stress response persistently, resulting in alterations of the hippocampus structure and function [28]. The GC exerts its physiological and pathological functions by activating GR and GR effects GCs.…”
Section: Effects Of Gc/gr/glucocorticoid Receptor Interacting Proteinmentioning
confidence: 98%
“…When stress affects the expression of GR in the hippocampus, the negative feedback regulation of the HPA axis will be affected. Many experimental studies have also confirmed that the presence of long-term increased GC will reduce the expression of GR, weaken the inhibition of the HPA axis and make the HPA axis stress response persistently, resulting in alterations of the hippocampus structure and function [28]. The GC exerts its physiological and pathological functions by activating GR and GR effects GCs.…”
Section: Effects Of Gc/gr/glucocorticoid Receptor Interacting Proteinmentioning
confidence: 98%
“…NO regulates a plethora of interactions between neuroimmune and neuroendocrine systems in physiologically normal and pathological conditions and neuronal nitric oxide synthase (nNOS) acts as a major modulator of processes governing the development of learning [241]. NO is involved in the regulation of corticosterone secretion and nNOS inhibits the activity of GR in the hippocampus resulting in the modulation of HPA axis activity [241, 242]. NO, in tandem with prostaglandins, plays a major role in enabling and regulating the activation of the HPA axis by CRH [243] (reviewed in [244]) and high NO levels exert broadly inhibitory effects [245].…”
Section: Factors Involved In Regulating Hpa Axis Activitymentioning
confidence: 99%
“…It is hypothesized that the application of different stressors and the specific durations of the stress may cause alterations in the GR expression in certain rodent strains [ 7 ]. Furthermore, previous studies have revealed that the levels of neuronal nitric oxide synthase (nNOS), an endogenous inhibitor of GR in the hippocampus, increase upon exposure to stress [ 8 ] and are involved in the regulation of the HPA axis activity via GRs [ 9 ]. Thus, the inhibition of nNOS in the hippocampus leads to the decrease of the CORT concentration in the plasma and reduced CRH expression in the hypothalamus.…”
Section: Introductionmentioning
confidence: 99%